In vitro characterization and in vivo detection of Rigidoporus lignosus, the casual agent of white root disease in Hevea brasiliensis, by ELISA techniques - Louanchi M; Balesdent M H; Despreaux D; Michels T; Robin P (European Journal of Plant Pathology, 1996)
A method for early detection of R. lignosus was developed. Two polyclonal sera were produced against soluble mycelial proteins of 2R. lignosus isolates, 1 from Africa (FCI2), the other from Asia (FID2). The specificity of the antisera was tested using isoelectric focusing (IEF)/Western-bolt and DAS-ELISA. The 2 sera recognized all 20 R. lignosus isolates from various geographical origins. The banding patterns obtained by Western-bolt enabled a distinction to be made between isolates from Africa and Asia. In DAS-ELISA and Western-bolt analyses, strong cross reactions were observed with R. ulmarius. Only slight reactions were observed in Western-blot analysis to R. lineatus and Phellinus noxius, both causative agents of root rot in Hevea. Cross reactions were not observed under the DAS-ELISA analysis conditions. No cross reactions were obtained with 9 other Polyporaceae or Hevea root pathogen species. The sensitivity threshold of the DAS-ELISA method was 5 ng/ml of R. lignosus protein. An initial approach to using the DAS-ELISA test for the detection of R. lignosus in infected plants was carried out on artificially inoculated root samples. The DAS-ELISA protocol enabled detection of R. lignosus in the root system of diseasesd plants. No cross reaction was observed with healthy plant extracts.
Source Year: 1996
Keywords: DAS-ELISA techniques; Hevea brasiliensis; In vitro characterization; In vivo detection; Rigidoporuslignosus; White root disease